Neonatal Jaundice: Knowledge, attitude beliefs, and practices of postnatal mothers in a tertiary care hospital in Uttarakhand, India - Aggarwal, Bindu; Agrawal, Archana; Chaudhary, Piyush; Gupta, Girish; Rana, Sudhir; Gupta, Sourabh (Indian Journal of Child Health, 2017)
Background: Neonatal jaundice (NNJ), a preventable cause of brain damage, is the most common cause of admission in the 1st week of life in neonatal intensive care unit. Objective: To determine the knowledge attitude and practices of postnatal mothers toward NNJ in tertiary care hospital. Materials and Methods: In this descriptive analytical study, 350 mothers who underwent delivery in our institute were interviewed within first 72 h of delivery using a structured questionnaire. Data were entered in Microsoft Excel 13 and analyzed with SPSS 23. Results: Mean knowledge score was 6.48±3.93 (0-21). 73% of the mothers knew the site of recognition in NNJ. However, inadequate knowledge regarding causes, danger signs of severity, complications and treatment were seen among respondents. At least one correct answer for cause, danger sign and complication of NNJ was reported by 28%, 54%, and 33% mothers, respectively. Only 8% mothers attributed it as a risk factor for death in the baby. Phototherapy and exchange transfusion as treatment modality was answered by 15% mothers only. Their knowledge score was significantly associated with parity, education level, residence, religion and previously affected babies but not with age. Regarding attitude, 20% mothers were willing to take the baby to the hospital within 24 h on recognition of jaundice, and almost 91% of those seeking medical advice were ready to follow it. Conclusion: Although awareness of NNJ was seen in the majority of mothers, there was a paucity of knowledge regarding causes, danger signs, and effective treatment available. Cultural beliefs and traditional infant care practices do have a significant impact on mothers. Special educational programs and involvement of electronic media are needed to increase the awareness of mothers regarding NNJ.